Mass transfer of organic substances in supercritical carbon dioxide - Hu, Miao; Benning, Rainer; Ertunc, Özgür; Delgado, Antonio; Nercissian, Vanusch; Berger, Andreas (Defect and Diffusion Forum, 2012)
In this work special attention is paid on the direct visualization of the diffusion process of oil droplets in supercritical carbon dioxide as well as a better characterization of the process by quantitative evaluation of the diffusion coefficients obtained with a shearing interferometer. Experiments are also to be carried out under microgravity in to improve the experiment condition where the influence of gravity-driven convection that usually dominates the transport process is minimized. © (2012) Trans Tech Publications.
UnivIS-Import:2015-04-16:Pub.2012.tech.ITC.stmmec.masstr
Keywords: Diffusion coefficient; Microgravity; Shearing-interferometer; Supercritical carbon dioxide